Effectiveness of a Dyadic Nursing Intervention on Women With Gynaecological Malignancies and Their Family Caregivers: A Randomized Controlled Trial - Yanli Ji; Chen Zhang; Qifei Che; Xiaomei Qu; Xin Wen; Li Piao (Journal of Advanced Nursing, 2026)
ABSTRACT Aim To evaluate the effectiveness of a dyadic illness management–based intervention (Dyadic Guidance and Empowerment Program, D‐GEP) in alleviating demoralization among women with gynaecological malignancies and their family caregivers during the hospital‐to‐home transition. Design An assessor‐blinded, two‐arm parallel randomized controlled trial with repeated outcome assessments. Methods Women‐caregiver dyads were recruited from a tertiary hospital in Changchun, China (June–August 2025) and randomly allocated to the intervention or control group (1:1). The intervention group received D‐GEP, comprising two pre‐discharge face‐to‐face sessions, a 4‐week WeChat‐based video education programme comprising 20 videos, and a dyadic telephone follow‐up conducted 3 weeks after discharge. The control group received standard discharge planning and a telephone follow‐up. Outcomes were assessed at baseline (T0), immediate post‐intervention (T1) and 3 months post‐intervention (T2). Data were analysed according to the intention‐to‐treat principle. Results A total of eighty‐four women‐caregiver dyads were recruited. Eighty women (95%) and 78 caregivers (93%) completed the full protocol. At 3 months, D‐GEP significantly reduced demoralization among both women and family caregivers compared with standard care, with large intervention effect sizes observed. In addition, the symptom burden of women and family caregiver burden were also significantly reduced, whereas dyadic mutuality and family hardiness (women‐reported) improved. However, no significant effect was found on women's self‐perceived burden. The intervention demonstrated high adherence rates and minimal attrition. Conclusion The D‐GEP effectively reduces demoralization and improves key dyadic outcomes for women with gynaecological malignancies and their family caregivers. Implications for the Profession and/or Patient Care Nurses can implement this theory‐driven dyadic programme to mitigate psychological distress and enhance mutual support, thereby facilitating improved continuity and quality of care during discharge and follow‐up. Impact To our knowledge, this study provides randomized controlled evidence that a theory‐driven dyadic intervention may effectively reduce demoralization among women with gynaecological cancer and their family caregivers during the transition from hospital to home care. The scalable D‐GEP model, combining brief in‐person sessions, video education and telephone follow‐up, offers a practical framework for oncology nurses to integrate dyadic care into routine discharge planning. These findings have important implications for oncology practice in Asian healthcare systems and other settings where family engagement is central to cancer care delivery. Reporting Method This study was conducted and reported in accordance with the CONSORT 2025 guidelines for randomized controlled trials. Patient or Public Contribution No Patient or Public Contribution. Trail Registration Chinese Clinical Trial Registry, No. ChiCTR2500104008. Registered on 10/06/2025, first recruitment on 20/06/2025.